Three spatially separate records confirm the presence of and provide a range extension for the giant pangolin Smutsia gigantea in Kenya - Tommy Sandri; Claire Okell; Stuart Nixon; Naomi Matthews; Fred Omengo; James Mathenge; Stephen Ndambuki; Daniel W.S. Challender; Richard Chepkwony; Patrick Omondi; Shadrack Ngene; Bradley Cain (Oryx)
Pangolins are some of the most overexploited but least studied mammals. The giant pangolin Smutsia gigantea is the largest of the eight pangolin species, measuring up to 180 cm in length and weighing up to 40 kg. It is a nocturnal, solitary species that occurs at low densities and little is known regarding its biology and ecology. It is distributed widely across the rainforests and forest savannah mosaics of equatorial Africa but its exact range extent is unknown. Apart from a single record in Kenya predating 1971, the eastern limit of its range was thought only to extend to central Uganda and western Tanzania. Here we present three spatially separate records confirming the presence of this species in Kenyan Afromontane forests. The three records are c. 120 km apart and c. 500 km east of the nearest confirmed giant pangolin population in Uganda. These records represent a significant range extension for the species and highlight the biodiversity and conservation importance of the Afromontane forests of western Kenya.